Sport performance and genetics - Kahn, A. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Obviously, the assertion according to which all men are born and remain equal in freedom and in rights, which comes from the French and American Revolutions of 1789 and is quoted in the preamble of the Charter of the United Nations, does not contest the reality of physical, psychical and cultural differences within human kind. Equality is not similarity. The concept of sport competition is precisely an illustration of this. Its "motto" is "May the best man win". In most fields, the best man is the strongest, the most resistant, the fastest, the nimblest… Now, such a quality does not only depend on will and determination but also, and, in reality mostly, on physical abilities. The average abilities of a tall and strong Scandinavian man for weight-lifting, shot put, javelin throwing or basketball, are obviously much higher than those of a Pygmy from Central-African Republic; and this statement of the obvious does not question by any means the assertion of all men's equality. In this extreme example of the Swedish giant and the short Black man, the determinism of different abilities, as that of physical characteristics, is of course of genetic origin. It is probable that genes' impact is also at stake in less typical situations. We think, of course, about the domination of Black male and female runners in sprint, about the over-representation of rangy subjects in endurance races… At that level, however, it is obvious that training intensity and techniques, on the one hand, mental strength, on the other, play an important part and interfere with the purely biological determinisms. Nonetheless, at the highest level, with an equal training and motivation, the best athlete is more likely to be the one who has the greatest physical abilities for that particular sport. Thereby, we must admit that sport logics promote the physical inequality of individuals, who are otherwise equal in dignity and in rights.